Using of Experiential Learning Model Based on Multimedia to Increase the Ability of Literation Writing Indonesian Poem in Elementary School - Cahyani, Isah; Sastromiharjo, Andoyo; D., Daris Hadianto (International Journal of Active Learning, 2017)
The education system in a country must be able to equip its young generation with sophisticated literacy skills, if they do not want to see individuals and their communities in poverty or poverty (PIRLS, 2007). The ability of literacy has become the center of attention has even become a crucial issue because of the ability of literacy related to the development of human resources in the future (PIRLS, 2007). This is because literacy skills are the key to success in school and the key to success to participate actively in the world of work, society, and politics. In the 2013 Curriculum, the competence expected from an SD / MI graduate is to have a productive and creative thinking and acting abstract and concrete. Writing is a productive action. Therefore, writing skills in Elementary School must continue to be nurtured and developed so that the expected graduate competence is achieved. Nevertheless, Alwasilah (2007) states that writing skills are the most neglected language skills in language education. This happens due to improper practice in writing lessons from elementary to university level. According to International Study of Achievement in Writen Composition (in Rahman, 2011), Indonesia is a country whose culture of writing and reading is still below average. The purpose of this study, namely to find out how the influence of multimedia-based Experiential Learning model on the ability of elementary students in writing poetry. Research method that the authors use is a quasi-experimental research method with a quantitative approach. To obtain research data, researchers used test instruments, observation sheets, and questionnaires. Quantitative approach is used to get a picture of the ability of students writing multimedia based with Experential Learning model. The result of the research, that is there is significant difference at the level of significance 0,05% between result of student learning in learning writing writing based on multimedia with Experiment Learning model with result of student learning not writing multimedia based with Experential Learning model .. Thus, It can be concluded that the model of multimedia-based writing learning with Experential Learning model. Can improve the ability to write Indonesian in elementary school. The writing ability of the experimental class is higher than the writing ability of the control class students.